Production Runs for Multiple Products: The Two-Product Heuristic - Saipe, Alan L. (Management Science, 1977)
The optimal solution is presented for the problem of determining production run sizes for two products which must be produced on the same machine. This solution forms the basis for a heuristic solution to the N product problem. This heuristic provides uniformly better results than the complete-cycle heuristic for this problem. Numerical examples are presented to illustrate the method.